1999
DOI: 10.1074/jbc.274.31.21491
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases

Abstract: The timely breakdown of extracellular matrix (ECM) 1 is essential for embryonic development, morphogenesis, reproduction, and tissue resorption and remodeling. The matrix metalloproteinases (MMPs), also called matrixins, are thought to play a central role in these processes. The expression of most matrixins is transcriptionally regulated by growth factors, hormones, cytokines, and cellular transformation (1, 2). The proteolytic activities of MMPs are precisely controlled during activation from their precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
2,872
1
124

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 3,813 publications
(3,023 citation statements)
references
References 85 publications
26
2,872
1
124
Order By: Relevance
“…Expression of several MMP genes is inducible with growth factors and cytokines including EGF (Nagase and Woessner, 1999;Westermarck and Ka¨ha¨ri, 1999). We showed that expressions of MMP-1, -3, -9 and -10 are inducible in T24 cells with EGF.…”
Section: Discussionmentioning
confidence: 78%
“…Expression of several MMP genes is inducible with growth factors and cytokines including EGF (Nagase and Woessner, 1999;Westermarck and Ka¨ha¨ri, 1999). We showed that expressions of MMP-1, -3, -9 and -10 are inducible in T24 cells with EGF.…”
Section: Discussionmentioning
confidence: 78%
“…MMP-9 has been associated with invasion and metastasis because of its potency to degrade gelatin and type IV collagen 8 as major components of basement membranes. To assess the clinical impact of MMP-9 expression on long-term survival in patients with operable NSCLC, an immunohistochemical study of MMP-9 expression by primary tumors was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…8,13 To date, activity of MMPs in tissue sections can only be measured using in situ zymography. 17,18 For this method however, fresh cryosections of primary tumors are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 In this regard, they are dissimilar from a group of bacterial proteinases that evolved a strict specificity for human IgA. 21 Also, IgG fragmentation with human and most bacterial proteinases has generally been found to be slower than with papain or pepsin.…”
Section: Introductionmentioning
confidence: 99%